Hyperreactio luteinalis during the third trimester of pregnancy. A case report - Reyna-Villasmil, Eduardo (2020)
Hyperreactio luteinalis is a rare entity of pregnancy characterized by bilateral and functional enlargement of the ovaries that present thin-walled cysts. Several hypotheses suggest it is caused by increased concentrations or ovarian sensitivity to chorionic gonadotropin. Many cases do not present symptoms or complications during pregnancy, and diagnosis is done accidentally by routine ultrasound. This rare benign condition is usually self-limited and resolves spontaneously following delivery. However, some have to be differentiated from malignant ovarian tumors by histological examination. Surgery is indicated when there are complications such as ovarian torsion or peritonitis due to hemorrhage or rupture. We present a case of hyperreactio luteinalis during the third trimester of pregnancy.